Healthy Gut, Healthy Bones: Targeting the Gut Microbiome to Promote Bone Health - Cooney, Olivia D.; Nagareddy, Prabhakar R.; Murphy, Andrew J.; Lee, Man K. S. (Frontiers in Endocrinology, 2021)
Over the past decade, the use of probiotics to modify the gut microbiome has become a public spotlight in reducing the severity of a number of chronic diseases such as autoimmune disease, diabetes, cancer and cardiovascular disease. Due to its popularity in the market, the commercial use of probiotics is outpacing the science. Our understanding of how exactly probiotics work in different diseases within the gut and how it affects other organs in the body is still in its infancy. In this mini-review, we take the opportunity to delve into how the different components of the gut work together and how the gut communicates with other organs, focusing on its role in bone homeostasis.